Untangling sources and deposition of airborne nutrients - Naimie, Lillian E., author; Collett, Jeffrey L., Jr., advisor; Fischer, Emily V., committee member; Schumacher, Russ, committee member; Baron, Jill, committee member; Willis, Megan, committee member (Colorado State University. Libraries, 2025)
Deposition of excess nutrients, nitrogen (N) and phosphorus (P), can have negative impacts on ecosystem health. This work will focus on frontiers in reactive N (Nr) and P deposition and emissions. Nr deposition in the US has experienced a regime shift, due to effective NOx emissions regulations, and is now dominated by reduced N (gaseous ammonia (NH3) and particulate ammonium (NH+4). Wet deposition of inorganic Nr is routinely measured by the National Atmospheric Deposition Program, and is of particular interest in sensitive ecosystems, including Rocky Mountain National Park (RMNP). Reduced inorganic Nr dominates wet Nr deposition in RMNP. Dry deposition of NH3 is rarely quantified due to the complexity in simulating its bidirectional exchange with surfaces. Bidirectional NH3 flux simulations require high time resolution NH3 concentration and micrometeorology data, both of which are technically challenging, costly, and generally unavailable. Here, we test whether more commonly available biweekly NH3 concentration data and meteorological reanalysis data can be substituted with acceptable results. Fluxes simulated with biweekly NH3 concentrations, commonly available from NH3 monitoring networks, underestimated NH3 dry deposition by 45%. These fluxes were strongly correlated with 30-minute fluxes integrated to a biweekly basis (R2 = 0.88), indicating that a correction factor could be applied to mitigate the observed bias. Application of an average NH3 diel concentration pattern to the biweekly NH3 concentration data removed the observed low bias. Annual NH3 dry deposition from fluxes simulated with reanalysis meteorological inputs exceeded simulations using in situ meteorology measurements by a factor of 2. Upslope flows driven by mountain-plains and synoptic-scale circulations frequently transport emissions from the Colorado Front Range urban corridor and nearby agricultural operations to RMNP. Spatial patterns of NH3 in this NE Colorado source region, from both satellite (IASI, Infrared Atmospheric Sounding Interferometer) and in situ observations, were strongly correlated with the number of animals in nearby confined animal feeding operations (CAFOs). Satellite observations reveal large increases over NE Colorado during the period 2013-2023, with increases over an agricultural region more than three times greater than over the Denver metro region. Decreases in particulate NH+4 formation, following emissions reductions in sulfur and nitrogen oxides, and increases in wildfire smoke are estimated to account for a small portion of the increase, which appears spatially to be dominated by increased emissions from agricultural sources. The western US is home to additional agricultural regions, ecosystems that are sensitive to excess inorganic Nr deposition, and increasing wildfire frequency. The effects of changing agricultural and smoke emissions are quantified using oversampled data from the Cross-track Infrared Sounder (CrIS), at 2 km resolution, for the warm season when peak agricultural emissions and wildfire frequency occur. The largest total column NH3 increases were associated with agricultural regions across the western US, ranging from a 1.5 to 4.8% increase per year. In the Colorado Front Range, the NH3 concentration trend above the agricultural subregion averaged 2.7% per year, decreasing to 2.5% per year when periods of wildfire smoke were removed. Over Idaho's Snake River Valley, the NH3 concentration trend of +1.5% per year did not change when smoke periods were removed. The spatial footprint of agricultural hotspots is increased by 7% per year across the western US from 2013 to 2023, a trend that may indicate expansion of agricultural activities, increasing lifetime of emitted NH3, or both, with important implications for increased NH3 deposition to nearby sensitive ecosystems. Research on the deposition of P is much more limited than N deposition, despite potential ecosystem impacts. The US NADP network has not previously quantified wet P deposition, in part due to a lack of a suitably tested method for trace-level measurements of ionic phosphate (PO3−4). Flow injection analysis, a well-established technique for measuring PO3−4 in surface water, is tested and optimized here for measurements down to < 1 μg P L−1. This technique was used to successfully quantify PO3−4 wet deposition from precipitation and snowpack samples, with concentrations ranging from below detection limit to 37.5 μg P L−1 in Colorado and Kentucky, laying important groundwork for a future national P monitoring effort.
Keywords: deposition; ammonia; phosphate